Design And Build Front End of Difa Rooms Application Using Laravel to Improve Wheelchair User Accessibility at Loans in Bandung City With Spiral Method - Fadilah, Rizky; Saputra, Muhardi; Alam, Ekky Novriza (eProceedings of Engineering, 2023)
Abstract- Bandung is the capital city of West Java and one of the cities included in the Top 50 Smart City, to be precise at 28. Having a population of 2,510,103 in 2020 makes the city of Bandung one of the most populous and developed cities in Indonesia where information needs for all residents of the city of Bandung is very important. However, with a number of approximately 6.9% of the population of Bandung city being disabled, information on the need for people with disabilities is still very minimal when the City of Bandung has entered as a smart city. Therefore, the research team created a website-based solution called Difa Rooms which is expected to later be able to provide information avenues for people with disabilities, especially wheelchair users, to get information about places that are accessible to people with disabilities. In this study, it is still devoted to lodging in the city of Bandung. Thus, the real goal of a smart city will be achieved without any community feeling isolated.Keywords- lodging, disabled, front-end, spiral, google lighthouse.